Differences between Pseudomonas aeruginosa in a clinical sample and in a colony isolated from it: Comparison of virulence capacity and susceptibility of biofilm to inhibitors - Ramos Vernieri, Alberto Nicolás (2010)
We study the differences between Pseudomonas aeruginosa from an infected wound (clinical strain) and a colony isolated from it. We assessed the in vitro inhibition of these P. aeruginosa biofilms by DNase and filtrate of Lactobacillus plantarum cultures (acid = AF and neutralize = NF) with crystal violet technique. Inhibition by AF was greatest than DNase for clinical and isolated strain (p<0.001) and greatest than NF for clinical (p<0.05) and isolated strain (p<0.001).Using a burn model in mice, we compared the infection producing by clinical and isolated strains in planktonic and biofilm form. Deaths were quantified and the infection was assessed by determining CFU/g of tissue in the lesion, spleen and liver.The infections with planktonic bacteria tended to become systemic and more deadly than biofilm infections. All infected wounds required the same healing period (30 days). These findings were independent of the origin of the bacteria (clinical or colony isolated strain). © 2008 Elsevier Ltd.